Les sciences et la nature sexuée du psychisme au tournant du xxie siècle - Odile Fillod (Genre, Sexualité et Société)
The idea that contemporary biomedical sciences testify to the existence of natural processes of sex differentiation of the human psyche is regularly expressed in public space. How can that be? Is it simply because scientific research has established the existence of such processes and continues to progress in understanding? Based on an analysis of the international scientific literature that could fuel that idea on one hand, and its popularization or invocation in the French media and popular literature on the other hand, this article argues that the existence of such processes is not proven and presents the social and structural factors that may explain why the contrary is nevertheless insistently stated.